Chemical control of Africanized Honey Bees (Apis mellifera) from the perspective of public health surveillance/ Control químico de las abejas melíferas africanizadas (Apis mellifera) en perspectiva de la salud pública/ Controle químico de abelhas... - Nassar, Rafael Salim; Lopez, Anderson Cornationi; Babolin, Lilian dos Santos; Gentil, Regina Célia; de Lima, Antonio Carlos Pedroso (Journal Health NPEPS, 2020)
Objective: to compare the time of the knockdown effect between the pesticides prallethrin and dichlorvos on Africanized Honey bees (AHB). Method: this is an experimental study. The effect of these two pesticides over time was evaluated based on a life table methodology. The probability of survival between the two groups was compared based on the Mantel-Cox test. Results: it was observed that within 40 seconds the estimated probability of survival (no knockdown) was approximately 20% for prallethrin and 70% for dichlorvos. Estimated probability of survival (no knockdown) for prallethrin was lower in comparison to dichlorvos up to approximately 90 seconds. After that, the estimated survival for both pesticides became closer and stable. After 300 seconds almost all AHB were eliminated by both pesticides. Prallethrin showed better effect to control AHB when compared to dichlorvos. Conclusion: based on the results and considering that prallethrin presents lower toxicity to humans and to the environment it can be a safer alternative rather than dichlorvos to control AHB in urban areas.